Role of microbial and phytoplanktonic communities in the control of seawater viscosity off East Antarctica (30-80° E) - Seuront, L; Leterme, SC; Seymour, JR; Mitchell, JG; Ashcroft, D; Noble, W; Thomson, PG; Davidson, AT; van den Enden, R; Scott, FJ; Wright, SW; Schapira, M; et al. (2010)
Despite the long-standing belief that seawater viscosity is driven by temperature and salinity, biologically increased seawater viscosity has repeatedly been reported in relation to phytoplankton exudates in shallow, productive coastal waters. Here, seawater viscosity was investigated in relation to microbial and phytoplanktonic communities off the coast of East Antarctica along latitudinal transects located between 30°E and 80°E in sub-surface waters and at the deep chlorophyll maximum (DCM). The physical component of seawater viscosity observed along each transects ranged from 1.80 to 1.95 cP, while the actual seawater viscosity ranged from 1.85 to 3.69 cP. This resulted in biologically increased seawater viscosity reaching up to 84.9% in sub-surface waters and 77.6% at the DCM. Significant positive correlations were found between elevated seawater viscosity and (i) bacterial abundance in sub-surface waters and (ii) chlorophyll a concentration and the abundance of flow cytometrically-defined auto- and heterotrophic protists at the DCM. Among the 12 groups and 108 species of protists identified under light microscopy, dinoflagellates and more specifically Alexandrium tamarense and Prorocentrum sp. were the main contributors to the patterns observed for elevated seawater viscosity. Our observations, which generalised the link previously identified between seawater viscosity and phytoplankton composition and standing stock to the Southern Ocean, are the first demonstration of increases in seawater viscosity linked to marine bacterial communities, and suggest that the microbially-increased viscosity might quantitatively be at least as important as the one related to phytoplankton secretion. © 2009 Elsevier Ltd.